2021
DOI: 10.1126/sciadv.abf0360
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase synthesis of benzene via the propargyl radical self-reaction

Abstract: Polycyclic aromatic hydrocarbons (PAHs) have been invoked in fundamental molecular mass growth processes in our galaxy. We provide compelling evidence of the formation of the very first ringed aromatic and building block of PAHs—benzene—via the self-recombination of two resonantly stabilized propargyl (C3H3) radicals in dilute environments using isomer-selective synchrotron-based mass spectrometry coupled to theoretical calculations. Along with benzene, three other structural isomers (1,5-hexadiyne, fulvene, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 99 publications
1
55
0
2
Order By: Relevance
“…In a side pathway, propene can also react with methyl radical and dehydrogenate to produce butene (C 4 H 8 , m/z 56) The propargyl radical is a key species that can react with (i) C 1 species to produce 1,3-butadiene, (ii) acetylene to produce cyclopentadienyl, or (iii) with another propargyl to produce the benzene (11) and fulvene (15). [6] The tunability of the VUV photon energy in iPEPICO allows us to confirm the formation of both C 6 H 6 isomers based on their IE (9.24 eV for benzene and 8.36 eV for fulvene). [7] The formation of C 3 species (CC 3 H 3 , CC 3 H 5 , CC 3 H 7 , C 3 H 4 , C 3 H 6 , and C 3 H 8 ) as well as C 4 H 6 are plausible mass growth pathways in methane conversion under non-oxidative conditions.…”
Section: Methodsmentioning
confidence: 86%
“…In a side pathway, propene can also react with methyl radical and dehydrogenate to produce butene (C 4 H 8 , m/z 56) The propargyl radical is a key species that can react with (i) C 1 species to produce 1,3-butadiene, (ii) acetylene to produce cyclopentadienyl, or (iii) with another propargyl to produce the benzene (11) and fulvene (15). [6] The tunability of the VUV photon energy in iPEPICO allows us to confirm the formation of both C 6 H 6 isomers based on their IE (9.24 eV for benzene and 8.36 eV for fulvene). [7] The formation of C 3 species (CC 3 H 3 , CC 3 H 5 , CC 3 H 7 , C 3 H 4 , C 3 H 6 , and C 3 H 8 ) as well as C 4 H 6 are plausible mass growth pathways in methane conversion under non-oxidative conditions.…”
Section: Methodsmentioning
confidence: 86%
“…Being that abundant, the propargyl radical could very well play an important role in the synthesis of aromatic molecules. For example, calculations indicate that the propargyl radical selfreaction can lead to cyclization, producing the aromatic radical phenyl radical at low temperatures (Miller & Klippenstein 2001;Zhao et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhao et al showed that molecular growth processes can occur via the reaction between two stabilized propargyl radicals at high temperature and diluted environments. Such a reaction can lead to the formation of benzene molecules, among other species [ 26 ].…”
Section: Introductionmentioning
confidence: 99%